Desmoid Fibromatosis of the Oesophagus Creating an Oesophageal Diverticulum in a 2-year-old Girl - Divya Murli; Vasundhara Smriti; Subhash Yadav; Bhakti Trivedi; Sajid S. Qureshi (Wolters Kluwer Medknow Publications, 2024)
Extra-abdominal desmoid fibromatosis arising from the oesophagus and the contemporaneous traction diverticula due to an oesophageal tumour is extremely rare. We present this complex situation in a 2-year-old girl which posed a surgical challenge requiring simultaneous management of multiple pathologies. Surgery addressed both the entities and the presence of the diverticulum facilitated achieving negative surgical margins.